Gamified Learning For Preschoolers: Exploring The Benefits And Risks Of Educational Apps In Indonesia - Ghisna Madina (Advances In Education Journal, 2025)
This study examines the benefits and risks of gamified learning apps for preschool children in Indonesia, where the use of technology among young learners is rapidly increasing. It reviews studies from 2018 to 2025 to show how gamified apps impact cognitive, emotional, social, and behavioral development. Results show that well-designed gamified learning tools increase motivation, problem-solving skills, executive function, and early literacy and numeracy skills. However, concerns persist that some apps are of low quality, encourage excessive screen time, or fail to align with children's developmental needs. Often, there is no parental or teacher guidance. Indonesia also faces limited culturally relevant apps, unequal access to quality digital resources, and low digital literacy among educators. This study calls for gamified learning resources that are developmentally appropriate, grounded in science, and tailored to the local context, with adults providing guidance on their use. It gives recommendations to parents, educators, developers, and policymakers to help safely and effectively integrate gamified learning in early childhood education in Indonesia.